2021
DOI: 10.21873/anticanres.14960
|View full text |Cite
|
Sign up to set email alerts
|

Have Volume-based Parameters of Positron Emission Tomography/Computed Tomography Prognostic Relevance for Patients With Potentially Platinum-responsive Recurrent Ovarian Cancer? A Single Center Italian Study

Abstract: Background/Aim: To assess the prognostic relevance of volume-based parameters [whole body (wb)metabolic tumor volume (MTV) and wb-total lesion glycolysis (TLG)] of pretreatment PET/CT in patients with potentially platinum-responsive recurrent ovarian cancer.Patients and Methods: This retrospective investigation analyzed 67 patients at first relapse. Results: At univariate analysis, post-relapse survival and overall survival correlated with residual disease after primary surgery (RD) (p=0.015 and 0.049, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For these patients, NACT gave them the opportunity for debulking surgery, reducing postoperative complications and ameliorating the optimal resection rate. A higher age and residual disease at PDS or IDS were independently poor prognostic factors for post‐relapse survival (HR 1.22, 95% CI 1.0–1.5, p = 0.026; HR 1.76, 95% CI 1.06–2.95, p = 0.031, respectively), 38,39 which might associated with comorbidities and intolerance to the standard chemotherapy dose in older patients and high susceptibility to chemoresistance in patients with initial residual lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For these patients, NACT gave them the opportunity for debulking surgery, reducing postoperative complications and ameliorating the optimal resection rate. A higher age and residual disease at PDS or IDS were independently poor prognostic factors for post‐relapse survival (HR 1.22, 95% CI 1.0–1.5, p = 0.026; HR 1.76, 95% CI 1.06–2.95, p = 0.031, respectively), 38,39 which might associated with comorbidities and intolerance to the standard chemotherapy dose in older patients and high susceptibility to chemoresistance in patients with initial residual lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MTV and TLG, as volume-based parameters, represent the metabolic activity across the tumor. Furthermore, whole-body MTV (WBMTV) and whole-body TLG (WBTLG) account for the metabolic burden of all lesions, offering a comprehensive view of the tumor’s functional activity ( 16 , 17 ). Lee et al reported TLG to be an independent predictor of progression-free survival (PFS) ( 18 ), but this observation was based on baseline PET/CT before treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic tumor volume (MTV), which is a volume measurement of tumor cells with high glycolytic activity, and total lesion glycolysis (TLG), which is the product of metabolic tumor volume (MTV) and mean standardized uptake value (SUV mean) of the lesion, both measure the overall change in tumor glycolysis. Additionally, WB-MTV and WB-TLG represent the sum of the metabolic burden of all lesions throughout the body, providing maximum multidimensional information of the lesions [6].…”
Section: Introductionmentioning
confidence: 99%